Managing the Web of Things : Linking the Real World to the Web - Benatallah, Boualem, editor; Qin, Yongrui, editor; Sheng, Quan Z., editor; Yao, Lina, editor; Ohio Library and Information Network (Cambridge, MA : Morgan Kaufmann, 2017)
Includes bibliographical references and index